Clinical study of vacuum-assisted excision of deep breast nodules via the retromammary space - Ma, Yuan-Yu; Xin, Hai-Na; Ren, Bin (Frontiers in Surgery, 2025)
ObjectiveTo compare the therapeutic efficacy of retromammary-space vacuum-assisted excision (VAE) and non-retromammary VAE for deep breast nodules ≤3 cm in maximum diameter, providing a clinical basis for selecting the optimal surgical approach.MethodsA retrospective analysis was conducted on the clinical data of 162 patients who underwent minimally invasive surgery for deep breast nodules at Weifang Maternal and Child Health Hospital between May 2022 and November 2024. Among them, 81 patients received retromammary-space VAE, while another 81 underwent non-retromammary VAE. Based on nodule size, the retromammary-space VAE group was further divided into two subgroups: the 0–2 cm group (n = 41, 0 < nodule ≤ 2 cm) and the 2–3 cm group (n = 40, 2 cm < nodule ≤ 3 cm). The two groups were compared in terms of operative time, intraoperative blood loss, number of punctures, and incidence of postoperative complications. Subgroup analysis within the retromammary-space VAE group further compared these parameters between the two size-based subgroups.ResultsCompared with non-retromammary VAE, retromammary-space VAE demonstrated statistically significant advantages (P < 0.05) in key parameters, including shorter operative time, less intraoperative blood loss, fewer punctures, and a lower incidence of postoperative complications. Subgroup analysis revealed that the 0–2 cm group had shorter operative time and less blood loss than the 2–3 cm group (P < 0.05), while the number of punctures did not differ significantly between groups (P > 0.05).ConclusionRetromammary-space VAE for deep benign breast nodules can effectively reduce intraoperative bleeding, shorten operative time, and lower the incidence of complications such as pectoralis muscle injury and hematoma. This technique allows precise puncture positioning beneath the nodule, minimizes the number of punctures, and maintains this advantage regardless of nodule size, demonstrating promising clinical applicability and potential for wider adoption.